Impact of Omalizumab in Patients with Severe Uncontrolled Asthma and Possible Predictive Biomarkers of Response: A Real-Life Study - Susana Rojo-Tolosa; María Victoria González-Gutiérrez; José Antonio Sánchez-Martínez; Gonzalo Jiménez-Gálvez; Laura Elena Pineda-Lancheros; José María Gálvez-Navas; Alberto Jiménez-Morales; Cristina Pérez-Ramírez; Concepción Morales-García (MDPI AG, 2023)
Most patients with asthma can control their symptoms with a basic standard of medical care and with maintenance and rescue medication. However, between 5% and 10% of asthmatics worldwide do not achieve control of their symptoms and have recurrent exacerbations and respiratory difficulties. The objective of the study was the real-life evaluation of the clinical improvement of patients with severe eosinophilic asthma treated with omalizumab, together with the search for biomarkers associated with the response. An observational retrospective cohort study was conducted that included patients with severe uncontrolled allergic asthma being treated with omalizumab. Three types of response were evaluated: lower use of oral corticosteroids, improvement in lung function, and reduction in exacerbations. A total of 110 patients under treatment with omalizumab were included, with a mean age of 48 ± 16 years. After 12 months had elapsed, significant reductions were found in the number of exacerbations, use of oral cortico-steroids and doses of inhaled corticosteroids (p < 0.001). Lung function and asthma control improved significantly (p < 0.001; p = 0.004) and eosinophil levels were significantly reduced (p = 0.004). Low scores in the Asthma Control Test were associated with the oral corticosteroid-saving effect; lower previous FEV1 levels and absence of chronic obstructive pulmonary disease (COPD) were related to improvement in lung function, and prior FEV1 values higher than 80% and absence of gastroesophageal reflux disease (GERD) with a reduction in exacerbations. The results of this study confirm the clinical benefit obtained after the introduction of omalizumab and the possible predictive biomarkers of response to the treatment.